PENGARUH IKLAN DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PADA KFC METROPOLITAN CITY PEKANBARU - Mahmudah, Riva Atul; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine how much influence advertising and brand image to consumer buying interest. Sampels in this study were taken as many as 100 respondens and techniques used accidental sampling approach. The data in this study using survey method through questionnares filled by consumers. Data were obtained by using simple regression analysis dan multiple regression analysis. The result of this study show that advertising has a significant impact on consumer buying interest. brand image has a significant impact on consumer buying interest. And then simultaneously advertising and brand image have a significant impact on consumer buying interest. Subsequent research is suggested to use other methods in researcing consumer buying interest, for example through in-depth interviews of respondentsKeywords: Advertising, Brand Image, And Consumer Buying Interest